THU0599 From Bad to Worse? The Impact of Switching Biologic Agents Multiple Times on Work Productivity and Health-Related Quality of Life for Patients with RA. (23rd January 2014) - Harrison, T.; Martin, L.; Barnabe, C.; Fyie, K.
Abstract : Background: We are interested in assessing the influence on work productivity in patients with RA who switch their biologic therapy due to lack of efficacy. Investigating the extent of this impact on patients with Rheumatoid Arthritis as they "cycle" through biologic therapies to achieve a well-controlled disease state contributes greatly to outcome evaluation. Objectives: To evaluate changes in employment and work productivity between patients who have not required a switch in therapy and those who have switched biologic agents. A secondary objective was to investigate the relationship of employment and work productivity and HAQ scores. Methods: Since 2000, the Alberta Biologics Pharmacosurveillance Program has captured clinical efficacy, safety and socioeconomic data in patients treated with biologic therapies. Patients complete HAQ and work productivity questionnaires every 6 months. HAQ scores and work productivity were evaluated in longitudinal analysis over the course of therapy. Results: Our cohort includes 2718 patients (male and female of all races, mean age 53 years) who have been treated with one or more biologic agent, including etanercept, infliximab, adalimumab, certolizumab pegol, golimumab, rituximab, abatacept and tocilizumab. Mean indices of disease activity at baseline were: DAS28 (ESR) 5.4, tender joint count 12.4 and swollen joint count 8.9 and HAQ 1.47. From this cohort, we compared employment status and HAQ scores between patients who switched biologic agents up to four times (self-reported employment status n=729, hours worked n=1766). Our results show that there is a reduced rate of employment and a reduction in hours worked in those patients who switched biologic therapies more than once. For patients showing a decrease of 0.2 in their HAQ over course of treatment, 76% remained employed if they did not switch compared to 54% who did. Conclusions: Patients who do not respond to biologic therapy experience a decrease in work productivity. These observations suggest that there needs to be an improved process to select the most effective agent when prescribing biologic therapies in RA patients. Disclosure of Interest: None Declared